Effect of Modifying Shellac with Citric Acid on Shellac-Bagasse Biocomposite - Nurhayati, Nanik Dwi; Wijaya, Karna; Triyono; Heraldyin, Eddy (Asian Journal of Chemistry, 2019)
This study was aimed at modifying local Shellac with citric acid in varied concentrations of 2, 4, 6, 8 and 10 % (w/w) to prepare Shellac-Bagasse (Sh-Bg) biocomposite and determining its physico-chemical properties. The biocomposite was made from the natural Shellac matrices and Bagasse fibers. Physico-chemical properties of non-modified Shellac and Shellac modified with citric acid including functional groups, intrinsic viscosity, density, and mechanical tensile strength were characterized using Fourier transform infrared spectrometer (FTIR), Oswald viscometer and Universal Testing Machine (UTM). The analysis results showed an optimum modification of shellac-citric acid at a concentration of 4% (w/w). FTIR analysis of the modified Shellac showed a broad absorption at 3448 cm–1 which indicated the presence of hydroxyl groups (-OH). The presence of C=O ester groups was indicated by the absorption appearing at 1712 cm–1. The absorption at 1251-1250 cm–1 indicated the presence of C-O groups, while the presence of -CH2 methylene groups was indicated by the absorption at 1465 cm–1. The modified Shellac with its optimal intrinsic viscosity of 169.97 mL/g indicated that there was a reaction between citric acid and Shellac to form an ester, so that the polymer chains formed were longer with a low density of 0,6662-0,8168 mg/L when compared to Shellac without modification. The low density indicated that the citric acid-modified Shellac could be processed to be biocomposite. The biocomposite was made with various compositions of Shellac and Bagasse with hot press at 80 °C and under a pressure of 6 Kgf/cm2. The optimum ratio of Shellac to Bagasse in Shellac-Bagasse (Sh-Bg) biocomposite was of 60:40 %. While, the analysis using Universal testing machine resulted a mechanical tensile strength of 0.6 MPa and an elongation at break of 0.45 %.